LA INVESTIGACION CIENTIFICA Y LOS JOVENES UNIVERSITARIOS - Ishiyama Cervantes y Cols., Raúl (2019)
The scientific research contributes with the development of the countries. In ours the young people who are interested in investigating are disturbed by the variety of methods that have appeared in the last years. In numerous books on methodology of the investigation, almost there is no similarity among them; the majority displays new terminology. There are institutions of superior education that dictate courses of scientific research complemented to an investigation seminary that implies several semesters of study. Each university has its own regulation by the autonomy, in some cases each Faculty; in the young people interested in investigating confusion takes place. The thesis projects delay months in being approved. One has verified by means of interviews, conversations, congresses, seminaries and encounter with students, that the return to the simple and natural investigation is giving positive fruits as much to scholastic level, university and professional. When the college students verified that to design a project, to develop it and to write the report in simple form is effective, more were interested in the scientific research. The students have verified that the investigators like Julio C. Tello, Honorio Delgado, Luis Pasteur, the Curie spouses, and Aristóteles too, investigated without the terminology and present rules; their works are considered investigation models.